RETRACTED: The Use of Digital Portfolio to Assess the Student Teachers’ Professional Skills - N. V. Tikhonova (Высшее образование в России)
RETRACTED ARTICLENowadays, digital technologies are widely used at all levels of education and are effectively integrated into diverse teaching and learning activities (transmission of information, educational projects, presentations, games, training, modeling, evaluation and competence assessment, etc.). Information and communication technologies are considered in this study as a key element of assessment of teacher student professional skills and competencies during school teaching practice. A digital portfolio is regarded as a form of authentic assessment of teaching practice and a way to improve teaching performance and to contribute to pre-service teachers’ professional growth. The purpose of the research is to analyze the opportunities and potential benefits as well as the disadvantages of using digital portfolio in teacher preparation course and to propose recommendations for the full realization of this method’s potential. The author analyzes the experience of Swiss teachers in using a digital portfolio to assess the results of student teaching practice. The research focuses on the role of the digital portfolio in developing the pre-service teachers’ ability to selfassessment and self-reflection.